(untitled) (The Gaze: Journal of Tourism and Hospitality, 2017)
Ecotourism gives priority to ecological resource integrity, environmental conservation, community development and economic development by maintaining low-impact and non-consumptive use of local resources. There are different forms of ecotourism developed worldwide as community based ecotourism, ecosystem ecotourism, cultural ecotourism, nature based ecosystem, protected area ecotourism and rural ecotourism. It focuses on meeting three concurrent goals of biodiversity conservation, poverty reduction and business viability using sustainable principles and practices. In sustainable ecotourism, local government officials, local communities, NGOs, private sector and management committee had a great role for tourism development and maintaining healthy cooperation and coordination. Ecotourism had more beneficial impacts compared to adverse impacts on the environment, society and culture. It emphasizes the protection of natural resources, biological diversity and sustainability of resource. It increases mobility of people, social stability and harmony; strengthen traditional culture, hospitality and folkway; and decreases political conflicts. Economic benefits from ecotourism include direct employment in hotels, lodges, tourist restaurants, and tourist chauff euring. It is an integral part of the master development strategy of a developing nation. In Nepal, ecotourism helps to enhance forest cover, flora, fauna, greenery, alternative energy sources, natural resource, biodiversity and other environmental benefits. It had helped in controlling antisocial activities, conserving religious and cultural heritage, maintaining peace and prosperity and increase in cooperation of people with religious beliefs and religious tolerance. It had a great role in poverty alleviation, rural development, agricultural transformation, community enrichment and social empowerment of women in Nepal. In the early stage of ecotourism development, it is difficult to have adequate private agencies and local people involved in delivering lodging, fooding, tour management and tourism activities during peak visitation season. There is need of training on nature guiding, cooking, sustainable use of tourism resources, proper handling of tourism demands, expertise in park management and finance management. THE GAZE JOURNAL OF TOURISM AND HOSPITALITY Vol. 8 No.1 Year 2017, page: 1-19